Calculation of charge density wave phase diagram by interacting eigenmodes method. (3rd August 2022) - Park, Changwon
Abstract: Patterns and periods of charge density waves (CDWs) in transition metal dichalcogenides exhibit complex phase diagrams that depend on pressure, temperature, metal intercalation, or chalcogen alloying. The phase diagrams have been understood in the context of Landau free energy model which explains the lock-in behavior in the commensurate–incommensurate phase transition and rotational symmetry breaking (stripe phase) in CDW phase. Here, we present that our interatomic potential energy function has not only reproduced the above behaviors in the temperature-dependent phase diagram of monolayer H-TaSe2 without adjustable parameters, but also predict a new commensurate–commensurate phase transition. For the calculation, eigenmodes of the lattice potential were used for variables in the interatomic potential and CDWs are obtained as ground states of interacting eigenmodes. Unlike Landau model, the parameters in our potential energy function are directly calculated from first-principles. Our work explicitly shows how the aforementioned behaviors in CDW phase transition are related with the lattice anharmonicity.